2014
DOI: 10.1016/j.ejmech.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Polyisoprenylated methylated protein methyl esterase: A putative biomarker and therapeutic target for pancreatic cancer

Abstract: Pancreatic cancer is the most deadly neoplasm with a 5-year survival rate of less than 6%. Over 90% of cases harbor K-Ras mutations, which are the most challenging to treat due to lack of effective therapies. Here, we reveal that polyisoprenylated methylated protein methyl esterase (PMPMEase) is overexpressed in 93% of pancreatic ductal adenocarcinoma. We further present polyisoprenylated cysteinyl amide inhibitors (PCAIs) as novel compounds designed with structural elements for optimal in vivo activities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…We previously reported the synthesis of polyisoprenylated cysteinyl amide inhibitors (PCAIs) for testing as potential anti-cancer agents [ 20 ]. PCAIs were designed to target polyisoprenylated methylated protein methyl esterase (PMPMEase), an enzyme which is overexpressed and hyperactive in lung cancer cells and tissues [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported the synthesis of polyisoprenylated cysteinyl amide inhibitors (PCAIs) for testing as potential anti-cancer agents [ 20 ]. PCAIs were designed to target polyisoprenylated methylated protein methyl esterase (PMPMEase), an enzyme which is overexpressed and hyperactive in lung cancer cells and tissues [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the synthesis of polyisoprenylated cysteinyl amide inhibitors (PCAIs) for testing as potential anti-cancer agents [ 20 ]. PCAIs were designed to target polyisoprenylated methylated protein methyl esterase (PMPMEase), an enzyme which is overexpressed and hyperactive in lung cancer cells and tissues [ 20 , 21 ]. We demonstrated that PCAIs are poor inhibitors of PMPMEase but potent inhibitors of cell viability, cell proliferation, and apoptosis in pancreatic cancer cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCAIs (NSL-BA-036, NSL-BA-040, NSL-BA-055 and NSL-BA-056) were synthesized in our lab as previously described [23]. CellTiter-Blue Cell Viability Assay kit, Caspase-Glo 3/7, Caspase-Glo 8 and Caspase-Glo 9 Assay kits were obtained from Promega.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of effective therapies against cancers driven by mutant Ras proteins coupled with the aggressiveness of such tumors maintains the impetus for the continuous search for novel therapies. This drive led us to develop the polyisoprenylated cysteinyl amide inhibitors (PCAIs) initially to suppress the activities of PMPMEase (Aguilar, Nkembo et al 2014) which we found to be overexpressed in lung and pancreatic cancers [22,23]. Remarkably, we observed that although the PCAIs only minimally inhibited PMPMEase [23], their potencies against cell viability and proliferation, angiogenesis, migration and invasion vastly surpassed their PMPMEase inhibition [24–27].…”
Section: Introductionmentioning
confidence: 99%